1947
DOI: 10.1038/bjc.1947.37
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding 7OH-2-Acetaminofluorene to Albino Rats

Abstract: A SURVEY of the carcinogenic action of 2-acetaminofluorene (AAF) has been recently published (Bielschowsky, 1947). In 1945 Bielschowsky isolated 70H 2-acetaminofluorene (70H-2AAF) from the urine of rats fed AAF. He considered that 70H-2AAF was not the only metabolite of AAF, but " the derivative which is excreted in the largest quantities in the urine.." In experiments of his in which 70H-2AAF was fed to rats for 62 weeks the substance did not show any carcinogenic activity.In the work now reported the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1948
1948
1988
1988

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Aroclor 1254 induces a number of xenobiotic oxidative activities [Alvares et al, 1973; Litterst and van Loon, 1974; Ecobichon and Comeau, 1974;Ong et al, 19801. Since ring oxidation of arylamines and arylamides is generally considered to be a detoxification process [Bielschowslq, 1947;Hoch-Ligeti, 1947; Morris et al, 1960;McCann et al, 19751, the induction of the activities that form these metabolites may decrease the mutagenicity of these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Aroclor 1254 induces a number of xenobiotic oxidative activities [Alvares et al, 1973; Litterst and van Loon, 1974; Ecobichon and Comeau, 1974;Ong et al, 19801. Since ring oxidation of arylamines and arylamides is generally considered to be a detoxification process [Bielschowslq, 1947;Hoch-Ligeti, 1947; Morris et al, 1960;McCann et al, 19751, the induction of the activities that form these metabolites may decrease the mutagenicity of these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Succinoxidase activity of rat liver slices decreased when p-dimethylaminoazobenzene was fed and was even lower in the resulting tumors. This decrease in activity was prevented by diets that retard carcinogenesis (183). A similar decrease in enzyme was not observed when homogenates were used in place of liver slices or when 2-acetylaminofluorene was fed (184).…”
Section: Tissue Changes In Neoplasiamentioning
confidence: 71%
“…Whether the difference in enlargement of the adrenals in the two irradiated groups is real is difficult to decide, as only the male rats of the hard irradiated group could be used for this comparison; female rats have always larger adrenals than males. In previous experiments (Hoch-Ligeti, 1947, 1948 on the effect of the adnministration of small doses of penetrating and soft X-rays on healthy rats it was found that the increases in adrenal weights of male rats were significant in both cases.…”
Section: Resultsmentioning
confidence: 91%